2018
DOI: 10.1002/dneu.22645
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of MET Receptor Tyrosine Kinase, an Autism Risk Factor, Impairs Developmental Synaptic Plasticity in the Hippocampus

Abstract: As more genes conferring risks to neurodevelopmental disorders are identified, translating these genetic risk factors into biological mechanisms that impact the trajectory of the developing brain is a critical next step. Here, we report that disrupted signaling mediated MET receptor tyrosine kinase (RTK), an established risk factor for autism spectrum disorders, in the developing hippocampus glutamatergic circuit leads to profound deficits in neural development, synaptic transmission, and plasticity. In cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…Gene ontology (GO) enrichment analysis of genomic neighbors has shown that most of these genes were enriched in a series of immune pathways, including cellular response to interferon-gamma, cellular response to interleukin-1, and positive regulation of the inflammatory response (Figure 2A; Estes and McAllister, 2015). KEGG pathway analysis illustrated the enrichment in the tyrosine metabolism pathway, which was consistent with the fact that MET receptor tyrosine kinase (RTK) is an autism risk factor ( Figure 2B; Ma et al, 2019). Together, these results indicated that ASD-related lncRNAs may be implicated in the pathogenesis of autism partly through immune response processes.…”
Section: Functional Enrichment Analysis Of Asd-related Lncrnassupporting
confidence: 70%
“…Gene ontology (GO) enrichment analysis of genomic neighbors has shown that most of these genes were enriched in a series of immune pathways, including cellular response to interferon-gamma, cellular response to interleukin-1, and positive regulation of the inflammatory response (Figure 2A; Estes and McAllister, 2015). KEGG pathway analysis illustrated the enrichment in the tyrosine metabolism pathway, which was consistent with the fact that MET receptor tyrosine kinase (RTK) is an autism risk factor ( Figure 2B; Ma et al, 2019). Together, these results indicated that ASD-related lncRNAs may be implicated in the pathogenesis of autism partly through immune response processes.…”
Section: Functional Enrichment Analysis Of Asd-related Lncrnassupporting
confidence: 70%
“…is an autism risk factor ( Figure 2B) [43]. Together, these results indicate that ASD-related lncRNAs may be implicated in the pathogenesis of autism partly through immune response processes.…”
Section: Functional Enrichment Analysis Of Asd-related Lncrnasmentioning
confidence: 60%
“…Several brain regions have been reported to be associated with the pathogenesis of ASD, such as cortex, frontal cortex (BA9), anterior cingulate cortex (BA24), cerebellum, hippocampus, hypothalamus and amygdala [6,43,45,46]. So we constructed specific weighted gene co-expression networks for these distinct brain regions, and then performed enrichment analysis using the pipeline described before, respectively.…”
Section: Differential Enriched Functional Terms Of Asd-related Lncrnamentioning
confidence: 99%
“…Both MET and CDKL5 are relevant to ASD. Using conditioned knockout mice and pharmacological inhibition, Ma and colleagues show that MET deficiency suppresses dendritic arborization and impairs dendritic spine formation and, moreover, they reveal that hippocampal plasticity is altered by MET deficits (Ma et al ., ). Thus, MET is critical for neuronal differentiation and maturation.…”
Section: Kinase Signaling In Neurodevelopmental Disordersmentioning
confidence: 98%